INFLUENCE OF PSM, GOAL CLARITY, JOB SATISFACTION, AND LEADER-MEMBER EXCHANGE ON OCB: MEDIATING ROLE OF EMPLOYEE ENGAGEMENT - Sinaga, Hebron Simson Yohanes Pande Raja; Pusparini, Elok Savitri (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study examines the impact of Public Service Motivation (PSM), goal clarity, job satisfaction, and leader-member exchange (LMX) on Organizational Citizenship Behavior (OCB), with employee engagement as a mediating variable. Grounded in the Job Demands–Resources (JD-R) model and Social Exchange Theory (SET), the research examines how motivational resources, role clarity, and relational quality foster engagement and, in turn, promote discretionary behaviors in public sector settings, particularly among immigration officers. Methods: Using a quantitative approach, data were collected from 368 immigration officers working in the immigration checkpoints division at four Class I Special Immigration Offices in Indonesia. A purposive sampling technique was applied, and covariance-based structural equation modeling (CB-SEM) was used to analyze relationships and test the mediating effect of employee engagement. Results: PSM, goal clarity, and LMX significantly influence OCB directly, while job satisfaction impacts OCB only through employee engagement. Employee engagement acts as a critical mediator, enhancing the effects of these variables on OCB. The results highlight the importance of employee engagement in transforming job satisfaction into meaningful organizational contributions. Conclusion and suggestion: The findings underscore the central role of employee engagement in translating PSM, goal clarity, job satisfaction, and LMX into voluntary, value-adding actions. For public sector managers, strategies to strengthen engagement by enhancing PSM, clarifying goals, fostering supportive leadership, and improving job satisfaction are essential for sustaining OCB, especially in high-pressure and disruption-prone service environments.